Proof Without Words: Independent Sets in Grid graphs and Tilings of Aztec Diamonds. Issue 2 (15th March 2019) - Butler, Steve
Abstract : Summary . A visual proof that the number of independent sets in the grid graphP 2 n □ P 2 n equals the number of tilings of the Aztec diamond An with rectangles where at least one of the dimensions is one.